Pengetahuan Perawat dan Penerapan Transcultural Nursing - Yellyanda Yellyanda; Ernawati Ernawati; Mursidah Dewi; Abbasiah Abbasiah (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the relationship between nurses' knowledge and the application of transcultural nursing in the Inpatient Room of Abdul Manap Hospital, Jambi City. This research method is an observational analytic study using a cross-sectional design. The results showed that of the 13 respondents who had good knowledge, 12 respondents (92.3%) had good transcultural, and of the 30 respondents who had poor knowledge, 22 respondents (73.3%) had poor transcultural. In conclusion, transcultural nursing is related to nurses' knowledge of therapeutic communication at the H.Abdul Manap Hospital, Jambi City. Keywords: Knowledge, Nurse, Transcultural Nursing